Elucidating the cellular uptake mechanisms of heptamethine cyanine dye analogues for their use as an anticancer drug‐carrier molecule for the treatment of glioblastoma. (29th November 2022) - Cooper, Elizabeth; Choi, Peter J.; Hwang, Kihwan; Nam, Kyung M.; Kim, Chae‐Yong; Shaban, Tina; Schweder, Patrick; Mee, Edward; Correia, Jason; Turner, Clinton; Faull, Richard L. M.; Denny, William A.; et al.
Abstract: The development of chemotherapies for glioblastoma is hindered by their limited bioavailability and toxicity on normal brain function. To overcome these limitations, we investigated the structure‐dependent activity of heptamethine cyanine dyes (HMCD), a group of tumour‐specific and BBB permeable near‐infrared fluorescent dyes, in both commercial (U87MG) and patient‐derived GBM cell lines. HMCD analogues with strongly ionisable sulphonic acid groups were not taken up by patient‐derived GBM cells, but were taken up by the U87MG cell line. HMCD uptake relies on a combination of transporter uptake through organic anion‐transporting polypeptides (OATPs) and endocytosis into GBM cells. The uptake of HMCDs was not affected by p‐glycoprotein efflux in GBM cells. Finally, we demonstrate structure‐dependent cytotoxic activity at high concentrations (EC50 : 1–100 μM), likely due to mitochondrial damage‐induced apoptosis. An in vivo orthotopic glioblastoma model highlights tumour‐specific accumulation of our lead HMCD, MHI‐148, for up to 7 days following a single intraperitoneal injection. These studies suggest that strongly ionisable groups like sulphonic acids hamper the cellular uptake of HMCDs in patient‐derived GBM cell lines, highlighting cell line‐specific differences in HMCD uptake. We envisage these findings will help in the design and structural modifications of HMCDs for drug‐delivery applications for glioblastoma. Abstract : Understanding the structure–activity relationships of HMCDs in patient‐derived glioblastoma cells will inform their design as drug‐delivery systems for the treatment of glioblastoma. HMCDs use a combination of organic anion‐transporting polypeptides and endocytosis to accumulate within glioblastoma cells but are not effluxed through p‐glycoprotein, with minimal toxicity in vitro .